2021
DOI: 10.31932/jees.v4i1.794
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Podcast to Promote Students’ Speaking Ability in Online Learning at the Covid Pandemic 19

Abstract: The objective of this research was to promote students' speaking ability by using podcasts in teaching and learning. the subject of the research was taken in one of the senior high schools in Bogor 11th grades and the participant was 6 students consists 3 of females and 3 of males. The method used in this study was Classroom Action Research (CAR), conducted in two cycles. The phases are planning, acting, observing, and reflecting as the process of teaching and learning. For collecting the data the researcher u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 5 publications
1
0
0
Order By: Relevance
“…As a result, given the variety of voices and tones employed in the application, the study emphasizes the relevance of employing this method in teaching English communication skills. More importantly, these findings are consistent with the findings of multiple earlier investigations (Mellisa et al, 2019;GP, 2020;Prasetya & Nuraeni, 2021;Saber et al, 2022).…”
Section: A First Questionsupporting
confidence: 92%
“…As a result, given the variety of voices and tones employed in the application, the study emphasizes the relevance of employing this method in teaching English communication skills. More importantly, these findings are consistent with the findings of multiple earlier investigations (Mellisa et al, 2019;GP, 2020;Prasetya & Nuraeni, 2021;Saber et al, 2022).…”
Section: A First Questionsupporting
confidence: 92%
“…This action research also indicated significant students' speaking skills improvement. Another learning material is podcasts that can help students promote their speaking skills since they are adequate for their vocabulary, pronunciation, and self-confidence (Perdana Prasetya & Nuraeni, 2021).…”
Section: Discussionmentioning
confidence: 99%